PF-06409577 Activates AMPK Signaling and Inhibits Osteosarcoma Cell Growth - Zhu, Yun-Rong; Zhang, Xiang-Yang; Wu, Qiu-Ping; Yu, Cheng-Jian; Liu, Yuan-Yuan; Zhang, Yun-Qing (Frontiers in Oncology, 2021)
Osteosarcoma (OS) is a common primary bone malignancy. We here investigated the potential activity of PF-06409577, a novel, potent and direct activator of AMP-activated protein kinase (AMPK), against human OS cells. In established (U2OS, MG-63 and SaOs-2 lines) and primary human OS cells, PF-06409577 inhibited cell viability, proliferation and migration, while inducing cell apoptosis and cell cycle arrest. PF-06409577 induced AMPK activation, mTORC1 inhibition, autophagy induction and multiple receptor tyrosine kinases (including PDGFRα, PDGFRβ and EGFR) downregulation in human OS cells. AMPK inactivation by AMPKα1 shRNA, CRISPR/Cas9 knockout, or dominant negative mutation (T172A) abolished PF-06409577-induced anti-OS cell activity. In vivo, PF-06409577 oral administration at well-tolerated doses potently inhibited growth of U2OS cells and primary human OS cells in severe combined immunodeficient mice. AMPK activation, mTORC1 inhibition, autophagy induction, as well as RTKs degradation and apoptosis activation were detected in PF-06409577-treated xenografts. In conclusion, activation of AMPK by PF-06409577 inhibits OS cell growth in vitro and in vivo.